Acupuncture for the Treatment of Adults with Posttraumatic Stress Disorder: A Systematic Review and Meta-Analysis. Issue 1 (1st January 2018) - Grant, Sean; Colaiaco, Benjamin; Motala, Aneesa; Shanman, Roberta; Sorbero, Melony; Hempel, Susanne
ABSTRACT: Acupuncture has been suggested as a treatment for posttraumatic stress disorder (PTSD), yet its clinical effects are unclear. This review aims to estimate effects of acupuncture on PTSD symptoms, depressive symptoms, anxiety symptoms, and sleep quality for adults with PTSD. We searched 10 databases in January 2016 to identify eligible randomized controlled trials (RCTs). We performed random effects meta-analyses and examined quality of the body of evidence (QoE) using the GRADE approach to rate confidence in meta-analytic effect estimates. Seven RCTs with 709 participants met inclusion criteria. We identified very low QoE indicating significant differences favoring acupuncture (versus any comparator) at post-intervention on PTSD symptoms (standardized mean difference [SMD] = −0.80, 95% confidence interval [CI] [−1.59, −0.01], 6 RCTs), and low QoE at longer follow-up on PTSD (SMD = −0.46, 95% CI [−0.85, −0.06], 4 RCTs) and depressive symptoms (SMD = −0.56; 95% CI [−0.88, −0.23], 4 RCTs). No significant differences were observed between acupuncture and comparators at post-intervention for depressive symptoms (SMD = −0.58, 95% CI [−1.18, 0.01], 6 RCTs, very low QoE), anxiety symptoms (SMD = −0.82, 95% CI [−2.16, 0.53], 4 RCTs, very low QoE), and sleep quality (SMD = −0.46, 95% CI [−3.95, 3.03], 2 RCTs, low QoE). Safety data (7 RCTs) suggest little risk of serious adverse events, though some participants experienced minor/moderate pain, superficial bleeding, and hematoma at needle insertion sites. To increase confidence in findings, sufficiently powered replication trials are needed that measure all relevant clinical outcomes and dedicate study resources to minimizing participant attrition.